Analisis Vegetasi Dan Cadangan Karbon Ekosistem Cemara Laut Sebagai Upaya Mitigasi Perubahan Iklim Di Pantai Muaro Kualo Bengkulu - Lisya Anggraini, Putri; Sulistiyani, Ani; Fatimatuzzahra, Fatimatuzzahra; Rahmawati, Pratiwi (Indobiosains, 2025)
The vegetation composition and structure influence the dynamic of coastal ecosystem at Cemara beach, Kualo Bengkulu. Vegetation play a key role in protecting the environment from natural disasters such as tsunamis, coastal erosion, wave, habitat destruction, and water degradation. Therefore, understanding it is crucial for providing data on coastal vegetation and the impacts of disturbances. This study aims to present baseline data on vegetation composition and structure and carbon stocks. This supporting sustainable coastal forest management as a coastal mitigation effort. The method used purposive sampling with quadratic-transec plot to analyzed vegetation, carbon stocks, and environmental factors. The measurement results are as follows: light intensity in shaded areas was 941 cd, in exposed areas 1465 cd, soil pH 6.8, temperature 36.3°C, wind strength 2.3 knots, and air humidity 58 Rh. Sampling was carried out by counting vegetation in the strata of stakes, poles, and trees. while carbon stocks were calculated in poles and trees. The study obtained 12 types of plants in details: the sapling  was dominated by Terminalia catappa (IVI: 61%), the poles were dominated by Pandanus utilis (IVI: 181.96) and the trees were dominated by Casuarina equisetifolia (IVI: 251.89).